International cooperation analysis of Asian political distance network constructed using event data - Sada, Sotaro; Oikawa, Keita; Iwasaki, Fusanori; Ikeda, Yuichi (Frontiers in Physics, 2022)
Economic integration is underway in East Asia and the Asia-Pacific region, including the Association of Southeast Asian Nations (ASEAN) community-building process, with the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) coming into effect in 2018 and the Regional Comprehensive Economic Partnership (RCEP) in 2022. While these Regional Trade Agreements (RTAs) have deepened multilateral relations, there is an insufficient mechanism to quantify multilateral diplomacy within the region. Therefore, this study analyzed the region from three perspectives: countries that have contributed to diplomacy for intra-regional cooperation (diplomatic ranking), the cohesiveness of countries in diplomatic stances (diplomatic clusters), and the synchronization period of cooperative events (diplomatic synchronization); and we quantified them by the ranking of diplomatic centrality, blockmodeling of the signed network, and analytic signal, respectively. For analysis, we used bilateral event data to create a political distance network consisting of original East Asia Summit (EAS) member countries (ASEAN+6) and the United States for the period 1985--2020 and to define diplomatic centrality. Diplomatic ranking indicated three major trends: 1985--1992, 1993--2011, and 2012--2020. Until 1992, Japan, ASEAN member states (AMS), and Australia ranked at the top, and from 1993 to 2011, Japan and China almost dominated the top. Since 2012, AMS has joined Japan and China in the top ranks. Diplomatic clusters showed the stances of Australia and New Zealand were closest. Throughout the 36 years, the stances of Japan and South Korea were also closer, followed by China, AMS, and the United States. Diplomatic synchronization quantified the progress of regionalism in East Asia. Furthermore, diplomatic rankings in synchronous periods revealed the difference between the diplomatic positions of Japan and China in East Asia and illustrated that the AMS was at the center of multilateral diplomacy in the region in 2018--2019.